Determinants of internal audit contribution to strategic management - Zainal abidin, Nor hafizah; Haron, Hasnah; Shahbudin, Amirul Shah (2010)
Recurrence of corporate scandals highlights the importance of an effective internal audit function to monitor and advice on strategic performance in tandem to financial performance. This study presumes that internal audit function contributes to strategic management due to its direct involvement in evaluating risks inherent to strategic objectives and its independent assistance in evaluating the organisational control systems (i.e. governance, risk management and control processes) that support the achievement of organisational objectives. Moreover, this study proposes that governance factors like internal audit quality, audit committee effectiveness, formalisation of risk management and status of internal control systems could influence the extent of internal audit contribution to strategic management.